PEMBERDAYAAN WARGA MELALUI PENDIDIKAN DAN PENYULUHAN KEWIRAUSAHAAN DI RT 02 RW 15 CLUSTER TAMAN HIJAU DESA SINDANGGALIH KARANGPAWITAN KABUPATEN GARUT - Andhika Lungguh Perceka, Andhika Lungguh Perceka; wahyudin; N. Ai Erlinawati (LP4M STIKes Karsa Husada Garut, 2020)
Community service through education, training, counseling and marketing digitally, processing various processed potatoes, bananas, and cassava. Execution method This community service is training. In this case, it provides training skills to make processed foods that have economic value, namely processed potatoes, bananas and bananas, cassava and ranginang. The implementation of community service was attended by 26 participants consisting of housewives. The results of the implementation of this community service can be concluded as follows: Housewives know and understand the importance of entrepreneurship benefits. Residents of RT 02 Cluster Taman Hijau are more skilled at understanding the process entrepreneurship. Citizens are able to make products/services from the process of ideas, planning, analysis needs, SWOT analysis and product marketing. Residents are still waiting for the arrival the service team to train other skills to increase their knowledge.